Pendampingan Penerbitan Sertifikasi Nomor Induk Berusaha (NIB) Untuk Peningkatan Legalitas dan Daya Saing UMKM Asinan di Kelurahan Nerogtog, Kecamatan Pinang Kota Tangerang - Fazira, Rabitha; Permana, Dean; izky, Daffa Andhika R (Jaanur ElBarik Indonesia, 2025)
This community service activity aims to provide understanding and assistance in issuing Business Identification Numbers (NIB) for Asinan MSMEs in Nerogtong Village, Pinang District, Tangerang City. This assistance method is carried out through training, technical guidance, and direct assistance using the OSS (Online Single Submission) system. The results of this community service activity can increase MSME awareness of the importance of business legality as capital for market development and expansion. This activity also improves legal compliance, strengthens business capacity, and supports the formalities of the MSME sector